A second species of the genus Panolcus Gerstaecker 1860 (Coleoptera: Curculionidae: Molytinae: Cryptorhynchini) from French Guiana and Suriname with taxonomic changes in Cryptorhynchini - Anderson, Robert S. (Zootaxa, 2024)
A second species of the genus Panolcus Gerstaecker, 1860 (Coleoptera: Curculionidae: Molytinae: Cryptorhynchini) from French Guiana and Suriname is described and compared with Panolcus scolopax Gerstaecker, 1860. Diagnostic characters and images are provided to facilitate identification. Adults were collected in a fruit of Duguetia surinamensis R.E. Fr. (Annonaceae). The genus Panolcus is transferred from Aedemonina (Cryptorhynchini) to Cryptorhynchina (Cryptorhynchini). The type species of Thrasyomus Pascoe, 1880 is here designated as Thrasyomus tumens Pascoe, 1880 and the species Thrasyomus uniformis Champion, 1905 is transferred from the genus Thrasyomus to Eubulus Kirsch, 1869 as Eubulus uniformis (Champion, 1905), new combination.